Pendidikan Moral dan Tantangan Teknologi: Implementasi Pancasila untuk Generasi Muda - Edy Sofyan; Rina Marlina; Feniawati Darmana (Journal on Education, 2024)
This study explores the role of Pancasila education in strengthening the nation’s moral sovereignty in the era of Society 5.0, where digital technology development has brought significant transformations to all spheres of social and economic life. Aiming to what role of Pancasila-based education play to shape students’ moral characters in the face of the moral and social challenges stemming from technology innovations, it mainly focused on how Pancasila-based education is able to strengthen the character of the students in collaboration with Pancasila moral in relation with sociology and social change. The research approached a qualitative method with structured interviews as its instruments, involving three of open-end structured interviewees who are purposively selected: education professionals, technology professionals, and non-formal educators. The results demonstrate formal and non-formal educational institutions are still insufficient to instill Pancasila values in the students, so they use the technology in wise and ethical ways. Furthermore, digitalization fosters more benefits, but not well-regulated with strong moral base will lift up the risk of ethics degradation and misinformation. All three interviewees agreed that moral values should be synergized between education institutes, society, and governments to effectively implement it in the digital age. The practical implication of the results is proposing education policies and regulations to minimize the negative impact of technology development. This research contributes to the moral education literature in the digital era and suggests further research directions on innovative teaching methods and adaptive policies in education due to technology advancements.